A survey on data stream, big data and real-time - Gomes E.H.A. (2019)
Copyright © 2019 Inderscience Enterprises Ltd.Real-time concept is being widely used by a society that seeks to speed communications, decisions and their daily activities. Even though this term is not used with the necessary conceptual precision, it makes clear the importance that time exerts on computer systems. Nowadays, the big data scenario, this concept is important and used with different meanings, which can define failure or successful of applications. This article aims to present a systematic literature review on the topics of data stream, big data and real-time. For this, we developed a protocol revision in which were determined research questions, the search term, the search source and the inclusion and exclusion criteria of articles. After an extensive study, we classify the articles selected in seven categories according to real-time concept used. Finally, we present a discussion that shows that there is not convergence on real-time concepts in the big data literature.